Access to Linked Administrative Data Through an Indigenous Cultural Lens - McBeth, Simon (International Journal of Population Data Science, 2020)
Introduction Stats NZ provides the world-leading Integrated Data Infrastructure (IDI) to help improve New Zealanders’ lives. Ngā Tikanga Paihere (the Tikanga Framework) is a tool designed to ensure data use is carefully considered, and practice occurs in good faith. It also aims to build and maintain public trust and confidence in the way Stats NZ manages administrative data in the IDI. It draws on general customary concepts from Te Ao Māori (Māori world) and sits in alignment with the current model of the Five Safes Framework for access. Objectives and Approach Tikanga are appropriate customary practices or ‘layers of the culture’ developed by Māori communities and individuals and informed by common cultural values and concepts. Stats NZ applies the framework when reviewing applications to use data in the IDI and Longitudinal Business Database (LBD). The framework is used with the original ‘Five Safes’ framework in the review process to ensure that data will be used in an appropriate and collaborative way, without marginalising any specific populations. In research proposals relating specifically to Māori, researchers are asked to demonstrate what value their work will bring to Māori communities and how the researchers will work collaboratively with those communities. Results Use of Ngā Tikanga Paihere has been well received. Stats NZ is now looking to broaden the use of Ngā Tikanga Paihere to assess all integrated data research proposals that focus on minority, identifiable, and marginalised populations. Conclusion / Implications While Ngā Tikanga Paihere does not resolve data governance or cultural licence issues, it encourages researchers to actively engage and collaborate with Māori groups when these communities are potentially impacted, or when the project might use data about these communities. Stats NZ sees data governance and cultural licence matters as an ongoing conversation between agencies and Treaty/Te Tiriti partners. Ngā Tikanga Paihere should be a tool to help guide the government data system to work with Māori data ‘in good faith’.